2020
DOI: 10.3390/fermentation6040123
|View full text |Cite
|
Sign up to set email alerts
|

Brewer’s Spent Yeast (BSY), an Underutilized Brewing By-Product

Abstract: The repurposing of by-products and the reduction of waste from food processing streams is an ever-increasing area of interest. Brewer’s spent yeast (BSY) is a prevalent by-product of the brewing industry. The spent yeast cells are removed at the end of the bulk fermentation. A small amount of it is used to start the next batch of fermentation; however, the majority of the spent yeast is discarded. This discarded yeast is high in nutrients, in particular proteins, vitamins and minerals, as well as containing fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 98 publications
0
47
0
5
Order By: Relevance
“…According to Vieira et al [218], the most common amino acids in spent yeast are alanine (even over 9%), arginine, aspartic acid, and cysteine. At the same time, Jaeger et al [219] indicated that glutamic acid is the most abundant one (~ 15%), followed by histidine, alanine, arginine, and aspartic acid. Such an effect may be associated with the differences between particular Saccharomyces cerevisae strains applied worldwide [220].…”
Section: Compositionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Vieira et al [218], the most common amino acids in spent yeast are alanine (even over 9%), arginine, aspartic acid, and cysteine. At the same time, Jaeger et al [219] indicated that glutamic acid is the most abundant one (~ 15%), followed by histidine, alanine, arginine, and aspartic acid. Such an effect may be associated with the differences between particular Saccharomyces cerevisae strains applied worldwide [220].…”
Section: Compositionmentioning
confidence: 97%
“…The ribonucleic acid is metabolized to the uric acid in the human body, which can cause gout [225]. Generally, the spent yeast application in animal and human nutrition was comprehensively discussed in dedicated review works [219,[226][227][228][229].…”
Section: Current Applications and Potential In Polymer Technologymentioning
confidence: 99%
“…Firstly, they have a sustainable and low-cost origin. Since viability of yeast is not crucial for encapsulation [ 31 ], under-utilized by-products such as spent yeast from beer making [ 40 ] can be employed. Secondly, they can be seen as safe and consumer-friendly products.…”
Section: Introductionmentioning
confidence: 99%
“…Spent yeast is another by-product from the brewing and biofuels industry. The spent yeast is typically removed at the end of the fermentation, although a small amount can be retained for subsequent fermentation batches [131]. Due to its protein content, discarded yeast is typically used as inexpensive animal feed materials [131].…”
Section: Spent Yeastmentioning
confidence: 99%
“…The spent yeast is typically removed at the end of the fermentation, although a small amount can be retained for subsequent fermentation batches [131]. Due to its protein content, discarded yeast is typically used as inexpensive animal feed materials [131]. However, spent yeast also contains valuable nutrients, such as vitamins (e.g., vitamins B 1 , B 2 , B 3 , B 6 , B 9 , and B 12 ) [132][133][134], minerals (e.g., Na, K, Ca, Mg, Fe, Mn, Zn, Cu, Se, Cr, and Mo) [134,135], proteins (e.g., mannoproteins and hydrolysates) [135], carbohydrates (e.g., β-glucans) [135], antioxidants (e.g., glutathione) [136], and phenolic compounds (e.g., gallic acid and (±)-catechin) [132].…”
Section: Spent Yeastmentioning
confidence: 99%